2020
DOI: 10.1101/2020.11.06.20225938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of home oxygen saturations as a marker of clinical deterioration in patients with suspected COVID-19

Abstract: Background The early identification of deterioration in suspected COVID-19 patients managed at home enables a more timely clinical intervention, which is likely to translate into improved outcomes. We undertook an analysis of COVID-19 patients conveyed by ambulance to hospital to investigate how oxygen saturation and measurements of other vital signs correlate to patient outcomes, to ascertain if clinical deterioration can be predicted with simple community physiological monitoring. Methods A retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Many patients hospitalised with acute covid-19 have severe hypoxia 478. Hypoxia, silent hypoxia, and the need for supplementary oxygen are all independent predictors of worse outcomes in covid-19 8910111213141516. Novel prognostic tools such as the 4C score have shown the importance of identifying hypoxia early,917 and there are physiological reasons for managing the complication promptly and actively 118…”
Section: Oxygen Levels In Covid-19mentioning
confidence: 99%
“…Many patients hospitalised with acute covid-19 have severe hypoxia 478. Hypoxia, silent hypoxia, and the need for supplementary oxygen are all independent predictors of worse outcomes in covid-19 8910111213141516. Novel prognostic tools such as the 4C score have shown the importance of identifying hypoxia early,917 and there are physiological reasons for managing the complication promptly and actively 118…”
Section: Oxygen Levels In Covid-19mentioning
confidence: 99%
“…Likewise, in South Korea, analysis of data showed that later presentation was associated with poorer outcomes, and countries such as Singapore, which had a policy of early admission to hospital, had a very low fatality rate [ 6 , 7 ]. Additionally, delayed admission and level of presenting oxygen saturation (SpO 2 ) in English patients has been shown to predict outcome, with even relatively small reductions of SpO 2 of 95% and below being associated with increases in mortality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have reported on SpO2 monitoring of at risk Covid-19 patients in a domestic “virtual ward” setting. One chose a threshold for admission of 2% less than a 96% target, [11]. Another did not find such monitoring useful because of variability of implementation, [12] whereas a third reported on remote monitoring of 26 patients after discharge from hospital with Covid-19,[13].…”
Section: Resultsmentioning
confidence: 99%